The bone shard daughter - Stewart, Andrea (Andrea G.) (Stewart, Andrea (Andrea G.). Drowning empire, 2020)
"The emperor's reign has lasted for decades, his mastery of bone shard magic powering the animal-like constructs that maintain law and order. But now his rule is failing, and revolution is sweeping across the Empire's many islands. Lin is the emperor's daughter and spends her days trapped in a palace of locked doors and dark secrets. When her father refuses to recognize her as heir to the throne, she vows to prove her worth by mastering the forbidden art of bone shard magic. Yet such power carries a great cost, and when the revolution reaches the gates of the palace, Lin must decide how far she is willing to go to claim her birthright--and save her people"--